Evaluation of the steel slag incorporation as coarse aggregate for road construction: technical requirements and environmental impact assessment. (1st September 2016) - Ferreira, Victor J.; Sáez-De-Guinoa Vilaplana, Aitana; García-Armingol, Tatiana; Aranda-Usón, Alfonso; Lausín-González, Cristina; López-Sabirón, Ana M.; Ferreira, Germán
Abstract: This work analyses the environmental impact of using electric arc furnace slags as secondary raw material in pavement and its comparison with the traditional materials used in road construction. Chemical and technical evaluations of the main characteristics of the black slags as coarse aggregate were carefully developed. The environmental analysis was carried out by using the Life Cycle Assessment methodology. The Life Cycle Inventory data was processed to obtain emissions grouped in terms of impact categories based on the Centre of Environmental Science of Leiden University baseline method at midpoint level. The results obtained revealed that some of the most relevant environmental impacts, such as carbon footprint, abiotic depletion, ozone layer depletion and photochemical oxidation, depend highly on the road construction processes, although, in the two scenarios analysed, the bitumen production was demonstrated to be the most contributing stage. These indicators also concluded that important environmental benefits could be obtained from the use of black slag as course aggregate in road construction. Consequently, the results shown here could be added to the list of technical criteria for their inclusion into a multi-objective optimisation methodology. Highlights: Use of electric arc furnace slag as a substitute of natural aggregates was analysed. Technical and chemical characterisations of the slags were addressed. These slags met the legal requirements to be used as aggregate in road construction. Natural and slag derived aggregates were compared by using life cycle assessment. The environmental impact of road construction can be reduced by using slags.